Analysis of Barriers to the Development of Islamic Educational Institutions in Kembangsri Ngoro Village, Mojokerto - Dinda Maula Miftahchul Hidayati; Budi Hariyanto (Universitas Muhammadiyah Sidoarjo, 2018)
Islamic educational institutions are considered to have more challenges than public schools. Besides the constraints of quality, relevance, elitism and management. Islamic educational institutions are actually trapped in decline, backwardness, powerlessness and poverty, as experienced by most of the Islamic countries and societies compared to non-Muslims. In Kembangsri Village, Ngoro District, Islamic educational institutions are less attractive to the surrounding community. They make Islamic educational institutions the last choice for their children if they are not accepted in public schools. So the purpose of this study was to identify and analyze the inhibiting factors and the efforts made in the development of Islamic educational institutions in Kembangsri Ngoro Village, Mojokerto. The type of research used is qualitative research. With the research subject, the Head of SMP Muhammadiyah 5 Ngoro and the Head of MI Darul Arqom Kembangsri. Data collection techniques were carried out by (1) observation, (2) interviews, (3) documentation. The results of the study indicate that the inhibiting factors in the development of Islamic educational institutions in Kembangsri Village lie in the management of institutional human resources, the principal who is less assertive in leading and the lack of institutional finance. Efforts that can be made by the institution are to improve management for the better, such as participating in trainings for the teacher council, adding extracurriculars to attract new prospective students, establishing cooperation with institutions related to education. Keywords: Analysis, Barriers, Development of Islamic Education.